Effect of glutamine supplementation on lymphocyte subsets in children with acute diarrhea - Yalçin, S Songül; Yurdakök, Kadriye; Tezcan, Ilhan; Tuncer, Murat (The Turkish Journal of Pediatrics, 2010)
To study the effect of glutamine supplementation on lymphocyte subpopulation counts in children with acute diarrhea, children aged 6-24 months were enrolled in a double-blind randomized study. Cases had received either 0.3 g/kg/day of glutamine or placebo orally for seven days. The counts of blood leukocytes, lymphocytes and lymphocyte subpopulations (CD3+, CD4+, CD8+, CD19+, CD16+CD56+) were determined both on admission and seven days later using a flow cytometry. When adjusting for sex, current breastfeeding status, dehydration, and nutritional status of children, lymphocyte subpopulations did not differ significantly between the glutamine- and placebo-supplemented groups on the 7th day of intervention.